2005
DOI: 10.1128/jcm.43.9.4789-4795.2005
|View full text |Cite
|
Sign up to set email alerts
|

Dot Enzyme-Linked Immunosorbent Assay for More Reliable Staging of Patients with Human African Trypanosomiasis

Abstract: Human African trypanosomiasis (HAT) or sleeping sickness is a disease characterized by a hemolymphatic stage 1 followed by a meningoencephalitic stage 2 which is fatal without specific treatment. Furthermore, due to the toxicity of drugs used to treat stage 2 (mainly melarsoprol) accurate staging is required. Actual criteria employed during field surveys are not sensitive enough for precise staging. Antineurofilament (anti-NF) and antigalactocerebrosides (anti-GalC) antibodies have been identified in cerebrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…There are also several promising developments in disease biomarkers (Papadopoulos et al 2004 ;Agranoff et al 2005). Blood or CSF markers for staging are in the early stages of development (Lejon et al 2002 ;Courtioux et al 2005) as are non-invasive diagnostic tools (Lejon et al 2006).…”
Section: Diagnostics and Chemotherapymentioning
confidence: 99%
“…There are also several promising developments in disease biomarkers (Papadopoulos et al 2004 ;Agranoff et al 2005). Blood or CSF markers for staging are in the early stages of development (Lejon et al 2002 ;Courtioux et al 2005) as are non-invasive diagnostic tools (Lejon et al 2006).…”
Section: Diagnostics and Chemotherapymentioning
confidence: 99%
“…106 Antibodies against neurofi laments, galactocerebrosides, neurofi laments, and glial fi brillary acidic proteins are also promising CSF markers of second-stage disease. [107][108][109] The diagnostic approach for T b rhodesiense disease diff ers from that for T b gambiense in several ways. First, there is no serological screening test for T b rhodesiense.…”
Section: Diagnosismentioning
confidence: 99%
“…Patients with central nervous system involvement during trypanosomiasis have been shown to have antibodies to galactocerebrosides in the cerebrospinal fluid that react with bovine galactocerebrosides (19). As in C. jejuni infection, in trypanosomiasis caused by Trypanosoma brucei, it has been suggested that anti-galactocerebroside antibodies cross-react with their mammalian counterparts (19). Furthermore, sera from patients infected with T. cruzi react with GSLs as well, although the specificity of those antibodies seems quite diverse (9).…”
Section: Parasitic and Protozoal Gslmentioning
confidence: 99%
“…Many Trypanosoma species contain neutral GSLs (97). Patients with central nervous system involvement during trypanosomiasis have been shown to have antibodies to galactocerebrosides in the cerebrospinal fluid that react with bovine galactocerebrosides (19). As in C. jejuni infection, in trypanosomiasis caused by Trypanosoma brucei, it has been suggested that anti-galactocerebroside antibodies cross-react with their mammalian counterparts (19).…”
Section: Parasitic and Protozoal Gslmentioning
confidence: 99%